Analisis Simbolisme Memorabilia Arsitektur Pada Pola Tatanan Ruang Luar Bangunan Museum - Gunawan, Valerie; Subiyantoro, Heru (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Symbolism in architecture can represent architectural elements and be configured for a specific purpose to communicate a certain image, value, or meaning to users or observers interacting with the building. The aspect of symbolism also represents memories of an event; the event is also formed and has a storyline. In commercial buildings, there is usually a sequence of outer space arrangements towards the main building, which can provide an experience for users. This research aims to analyze the symbolism contained in architectural memorabilia in the pattern of outer space arrangements in the building site, as well as to understand its influence on users and society. The method used in the preparation of this article is direct survey, interviews with relevant parties, and literature study of qualitative journals. The results show that symbolism in architectural memorabilia can include certain cultural, historical, and religious connotations that influence the identity, emotions, and image of individuals and groups interacting with the building. These symbols can evoke feelings of admiration, pride, or tranquility and can be catalysts in building emotional bonds between users and the outer space of the building.